An Analysis of Speech Act Used in Enola Holmes Movie - Mega Putri Agatha Karaeng; Galuh Dwi Ajeng; Hajjah Zulianti; Dian Windriani (Universitas Pamulang, 2024)
Miscommunication about the meaning of words in relation to the context of a situation is a common problem faced by both speakers and hearers. It was interesting in finding out about how language functions in human interaction, taking into account the context that affects communication as well as the intents behind utterances. Then, this research aims to identify the types of speech acts used; the most dominant types; the intended meanings of speech acts employed by Enola Holmes in the movie